2016
DOI: 10.1007/s00210-016-1235-5
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells

Abstract: Cisplatin is a well-studied and widely used chemotherapeutic agent and is effective in the treatment of the advanced human non-small cell lung cancer (NSCLC). Curcumin is a yellow pigment derived from the rhizome of Curcuma longa and has been proved to have antioxidant and antitumor properties. XRCC1 is an important scaffold protein involved in base excision repair and plays an important role in the development of lung cancer. In this study, we characterize the role of curcumin in the cytotoxicity, p38 MAPK ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…These findings are consistent with the results of the cell apoptosis assay. Previous studies [31][32][33] suggested that MAPKs can be induced by various compounds and are involved in cell death in NSCLC cells. The MAPK family includes three kinase members including JNK/stress activated protein kinases, P38mapk, and ERK [34].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…These findings are consistent with the results of the cell apoptosis assay. Previous studies [31][32][33] suggested that MAPKs can be induced by various compounds and are involved in cell death in NSCLC cells. The MAPK family includes three kinase members including JNK/stress activated protein kinases, P38mapk, and ERK [34].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Our analysis further revealed that the XRCC1 upregulation was mediated via MAPK phosphorylation. It has been reported that XRCC1 expression is dependent on ERK and p38 activation in non‐small‐cell lung cancer cells . The DNA damage can be repaired by BER or other DNA repair proteins, and cell cytotoxicity and drug resistance can be modulated between these DNA repair pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AMPK activation and 5-FU synergistically enhanced the antitumor effects of 5-FU on different types of cancer cells [ 17 , 18 , 35 ]. Another study demonstrated that enhancement of the cytotoxicity to cisplatin by administration of curcumin, an anti-inflammatory molecule in the turmeric root, is mediated by the downregulation of the expression levels of XRCC1 in human lung cancer cells [ 36 ]. In this study, inhibition of Akt activation, and CXCR4 and XRCC1 expression by AICAR, enhanced the 5-FU-induced cytotoxicity in CRC cells.…”
Section: Discussionmentioning
confidence: 99%